Evolution, Epidemiology and Etiology of Temporomandibular Joint Disorders - Sujata M Byahatti (Wolters Kluwer Medknow Publications, 2010)
The temporomandibular joint (TMJ) is unique to mammals, but among different mammalian groups, its morphology and function vary enormously. It is likely that various species show less loading of jaw joints during chewing than humans do. It took approximately 130 million years for the evolutionary process to stabilize this composite, basic vertebrate head skeleton to the jaws. Very little documentations are noted on anthropology of TMJ. When it is concerned with epidemiology, temporomandibular disorders (TMDs) have a number of consistent findings and various causative factors that can contribute to TMDs. The aim of the following article is to provide detailed information regarding its evolution, epidemiology and various causative factors leading to TMDs. Key Message: The masticatory system is extremely complex.